Tick borne encephalitis (TBE)-vaccination coverage and analysis of variables associated with vaccination, Sweden. Issue 38 (11th September 2015) - Askling, Helena Hervius; Insulander, Mona; Hergens, Maria-Pia; Leval, Amy
Highlights: Fifty-three percent of respondents ( n  = 4307) reported being vaccinated against TBE at least once. Higher income was associated with higher probability of vaccination (OR 2.10 95% CI 1.6–2.73). TBE-incidence in unvaccinated population was comparable with European high endemic areas. Abstract: To estimate the tick borne encephalitis (TBE)-vaccination coverage in the greater Stockholm region, we sent a questionnaire to a randomized sample of 8000 individuals in 2013. Fifty-three percent of all respondents ( n  = 4307) reported being vaccinated against TBE at least once. Reasons for not vaccinating included: no perceived risk (28.6%), too expensive (25.6 %), did not have the time or opportunity (23%) and worried about vaccine side-effects (20.5%). Multiple logistic regression revealed that the probability of being vaccinated was higher among those who reported ≥2 weeks outdoor exposure in a known high risk area (OR 4.13 95% CI 3.54–4.81) and in individuals ≥60 years of age compared to all other age groups (OR 0.67 95% CI 0.55–0.81). A high net household income was associated with a higher probability of being vaccinated (OR 2.10 95% CI 1.6–2.73). Being born outside Europe was negatively correlated (OR 0.57 95% CI 0.39–0.83). Based on our findings the estimated TBE-incidence in the unvaccinated regional population was 8.5-12/100, 000 which is comparable with high endemic areas as the Baltic region and Central Europe. We suggest targeted vaccination and reimbursement strategies in high-endemic areas of Sweden. Our results indicate a need for improved public information about TBE.